Cognitive and psychological resilience of students facing fire risk: implications for mental health and educational wellbeing - Sandu, Mihaela Luminița; Călin, Mariana Floricica; Matei, Raluca Silvia (Frontiers in Education, 2026)
AimIn contemporary society, exposure to natural and technological hazards, such as fires, poses significant challenges for mental health and for the effective functioning of educational and organisational institutions. The literature highlights that risk perception is a central determinant of adaptation processes, being closely linked to multiple dimensions of resilience.Objectives/hypothesesThis study aimed to analyse the relationship between fire risk perception and individual resilience, integrating psychological, cognitive, adaptive, and institutional dimensions. Four hypotheses were formulated: H1 – risk perception predicts resilience levels; H2 – cognitive resilience mediates the relationship between risk perception and psychological resilience; H3 – knowledge of intervention procedures mediates the relationship with adaptive resilience; H4 – institutional resilience moderates the relationship between risk perception and overall resilience.MethodologyThe sample consisted of 86 participants, primarily residents of Constanța County. Data were collected using the “Natural Disaster Resilience” questionnaire and analysed with SPSS 28, applying multiple regressions, mediation models (PROCESS Model 4), and moderation analyses (PROCESS Model 1).ResultsAnalyses revealed that risk perception significantly predicted all resilience dimensions (ηp2 = 0.972). The relationship between risk perception and psychological resilience was inversely mediated by cognitive resilience. Knowledge of intervention procedures mediated the relationship between adaptive resilience and expertise, while institutional resilience significantly moderated the link between risk perception and overall individual resilience.ConclusionThe study confirms an integrative model of resilience, in which risk perceptions, cognitive and emotional resources, operational preparedness, and institutional support interact to foster mental health and effective adaptation in the face of critical situations.